Pengaruh Kelas Ibu Hamil terhadap Pengetahuan tentang Kehamilan - Kasmiati Kasmiati (STIKes Ibnu Sina Ajibarang, 2024)
The Pregnant Women Class is an activity to discuss the contents of the Maternal and Child Health (MCH) Handbook in the form of group face-to-face meetings, followed by discussions and experience-sharing between pregnant women and health workers. The goal is to improve the knowledge and skills of mothers regarding pregnancy, childbirth, postpartum care, postpartum family planning, prevention of complications, newborn care, and physical activities/exercises for pregnant women. The type of research used is an intervention study targeting pregnant women using a